2010
DOI: 10.1186/1471-2458-10-245
|View full text |Cite
|
Sign up to set email alerts
|

Shamba Maisha: A pilot study assessing impacts of a micro-irrigation intervention on the health and economic wellbeing of HIV patients

Abstract: BackgroundHIV/AIDS negatively impacts poverty alleviation and food security, which reciprocally hinder the rapid scale up and effectiveness of HIV care programs. Nyanza province has the highest HIV prevalence (15.3%), and is the third highest contributor (2.4 million people) to rural poverty in Kenya. Thus, we tested the feasibility of providing a micro-irrigation pump to HIV-positive farmers in order to evaluate its impact on health and economic advancement among HIV-positive patients and their families.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 14 publications
0
25
0
Order By: Relevance
“…Future research could further clarify the mechanisms by which adolescents are more likely to enroll with low BMI. Furthermore, interventions to directly improve the nutritional status of underweight persons (Mamlin et al, 2009) and structural interventions that improve food access, such as agricultural production projects (Pandit et al, 2010), may be imperative to the overall success of HIV/AIDS and nutrition support programs.…”
Section: Resultsmentioning
confidence: 99%
“…Future research could further clarify the mechanisms by which adolescents are more likely to enroll with low BMI. Furthermore, interventions to directly improve the nutritional status of underweight persons (Mamlin et al, 2009) and structural interventions that improve food access, such as agricultural production projects (Pandit et al, 2010), may be imperative to the overall success of HIV/AIDS and nutrition support programs.…”
Section: Resultsmentioning
confidence: 99%
“…As an example of this approach, a small study in rural Kenya showed that an intervention that used a microirrigation water pump combined with a microfinance loan led to increases in crop yields, household income, BMI, and CD4 counts (189). More research is needed on structural interventions to address the root causes of poverty and food insecurity, to improve HIV health outcomes, and decrease HIV transmission risk (26,49,90,182).…”
Section: Need For Intervention Studiesmentioning
confidence: 97%
“…International experts call for sustainable approaches addressing drivers and consequences of food insecurity such as agricultural and other livelihood approaches. In this study, we conducted a pilot cluster RCT to assess the effects of a multisectoral agricultural and finance intervention we initially developed and evaluated in a small feasibility study [19], on health outcomes among people living with HIV/AIDS [PLHIV] in rural Kenya.…”
Section: Introductionmentioning
confidence: 99%